Deforestation Study in Kodagu District of Karnataka Using Landsat MSS Data - Lal, J. B.; Singh, Joginder; Gulati, A. K.; Prajapati, R. C. (Indian Forester, 1990)
Though forests are considered a valuable and renewable resource, yet its exploitation for quick monetary gains has been going on unabated. Large scale deforestation all over the country has attracted wide attention of the people and the Government. For taking remedial measures, it is necessary that extent of deforestation that is taking place be monitored. Comparison of multi-date remotely sensed data offers a tool to study and identify deforestation sites. In the present study, extent of deforestation in Kodagu district of Karnataka between 1982 and 1986 has been assessed by interpreting MSS satellite images on 1: 250,000 scale.